Characterization of equipment for shaping and imaging hadron minibeams - Pugatch, Valery; Brons, Stephan (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2017)
For the feasibility studies of spatially fractionated hadron therapy prototypes of the equipment for hadron minibeams shaping and monitoring have been designed, built and tested. The collimators design was based on Monte Carlo simulations (Gate v.6.2). Slit and matrix collimators were used for minibeams shaping. Gafchromic films, micropixel detectors Timepix in a hybrid as well as metal mode were tested for measuring hadrons intensity distribution in minibeams. An overall beam profile was measured by the metal microstrip detector. The performance of a mini-beams shaping and monitoring equipment was characterized exploring low energy protons at the KINR Tandem generator as well as high energy carbon and oxygen ion beams at HIT (Heidelberg). The results demonstrate reliable performance of the tested equipment for shaping and imaging hadron mini-beam structures.